Pharmaceutical Pricing and Reimbursement Policies in Sweden - Moïse, Pierre (OECD Publishing, 2007)
This paper examines aspects of the policy environment and market characteristics of the Swedish pharmaceutical sector, assesses the degree to which Sweden has achieved certain policy goals, and puts forth some key findings and conclusions. Thanks to low mark-ups in the distribution chain and no VAT for prescribed medicines, Sweden's public prices for pharmaceuticals are relatively low, in contrast to average prices received by manufacturers, which are among the highest in Europe. Recent reforms have helped to restrain pharmaceutical expenditure growth, following a period of double digit growth in the 1990s. Pharmaceutical expenditure per capita in Sweden is lower than the OECD average. Only five OECD countries devote less of their national income to pharmaceuticals. What limited evidence exists tends to suggest that relatively low pharmaceutical expenditures in Sweden are due to its low public prices, rather than to low levels of consumption. Sweden introduced a new pricing and reimbursement scheme in 2002. Its main features are the use of cost-effectiveness analysis for determining the reimbursement status of new pharmaceuticals and mandatory substitution of the lowest-cost generic alternative. The use of cost-effectiveness analysis in reimbursement decisions helps to relate the reimbursement price paid to the social value of the product, but does not necessarily result in the lowest possible price.The generic substitution policy has enabled Sweden to achieve fairly high penetration of generic drugs into the market in terms of volume, with a considerably low share of the total value of the market. However, the requirement to substitute only the lowest-priced listed drug risks undermining the competitiveness of the generic drug industry...
Keywords: Social Issues/Migration/Health; Sweden